Migrant readers and wordless books: visual narratives' inclusive experience - Giorgia Grilli; Marcella Terrusi (University of Bologna, 2014)
The research here told is the Italian contribution to the international project Visual Journeys: Understanding Immigrant Children's Response to Visual Images in Picturebooks, Conducted in Scotland, Arizona, Spain and Australia as an Observation of the Response of Migrant ten-eleven years old Readers to the Wordless Book The Arrival by Shaun Tan (2006). Reflections are made about co-construction and negotiation of meaning in a shared reading; wordless book is experienced as occasion of empowerment for those involved, giving value to individual stories and showing a positive outcome in school life, as for self-esteem and reciprocal relationships; it promotes discussion and increases interest in books, it shows an important effect on learning a foreign language and creating a group. The perspective of the whole experience is an interdisciplinary approach. The reading of wordless or silent book can be a true practice of right and belonging to the international community, and therefore a precious means for an education to global citizenship.